Financial Analysis of Additional Supply to Obtain Optimal Basic Costs of Provision in The Weda System - Sulaeman, Maman (International Journal of Social Service and Research, 2024)
The electricity growth in the PLN Weda Customer Service Unit (ULP) area in Central Halmahera Regency reached 26.64% in 2022, driven by national-scale nickel mining, resulting in consistent yearly increases in electricity demand. ULP Weda's electricity supply, with an installed power of 5.2 MW and a peak load of 5.6 MW, faces challenges due to high fuel prices, leading to a Cost of Supply (BPP) value of IDR 4,193, significantly higher than the average selling price of IDR 1,365 in the Veda system. To address these issues, a research methodology, incorporating SWOT and TOWS analyses, was employed. Three potential scenarios emerged: relocating Diesel Generating System (SPD) engines, adding rental generator engines, and purchasing excess power. Financial Feasibility Study (KKF) calculations, considering Nett's Present Value (NPV), Nett's Present Cost (NPC), and Internal Rate of Return (IRR), determined the excess power purchase scenario as the most viable, with an NPV of IDR 29.8 billion, NPC of IDR 623 billion, IRR of 33.49%, and the lowest BPP value at IDR 1,244. The Homer application provided insights into optimizing generating machine units for optimal BPP values. Sensitivity analysis showed that higher interest rates and lower fuel prices contribute to lower BPP values. This comprehensive research offers a strategic framework for addressing electricity supply challenges in the ULP Weda area, ensuring financial viability and optimal operation.